Pengaruh Model Pembelajaran Berbasis Proyek terhadap Siswa pada Mata Pelajaran PAI di SMPIT Aulia Muara Bulian - Sarbani, Sarbani; Saman, Saman; Roslini, Roslini (ISLAMIKA, 2024)
This study aims to evaluate the effectiveness of the project-based learning model in enhancing students' critical thinking skills in Islamic Religious Education (PAI) subjects in the fifth grade at SMPIT AULIA Muara Bulian,. The research method employed is true experimental with a quantitative approach. The study involves two groups: an experimental group that receives project-based learning and a control group that does not. Research instruments include pretests and posttests validated by experts. Statistical tests include normality tests, homogeneity tests, hypothesis testing using simple regression analysis, and Independent Sample t-Test. The research results indicate that the project-based learning model is effective in enhancing students' critical thinking skills. The experimental group showed significant improvement in posttest results compared to the control group. The normality and homogeneity tests indicated that the data were normally distributed and had homogeneous variance, thus valid for further analysis. Based on these findings, it is recommended that the project-based learning model be more widely implemented in PAI education to develop students' critical thinking skills from an early age.